Optimization of enzymatic hydrolysis condition of Angelwing Clam (Pholas orientalis) meat using Alcalase® to obtain maximum degree of hydrolysis - Amiza Mat Amin,; Cheng, Soong Kang (Penerbit Universiti Kebangsaan Malaysia, 2019)
Optimization of enzymatic hydrolysis conditions of angelwing clam (Pholas orientalis) meat (ACM) catalysed by Alcalase® to obtain the maximum degree of hydrolysis (DH) was carried out using Response Surface Methodology (RSM). A three level face-centered central composite design (CCD) was employed. Four independent variables of enzymatic hydrolysis conditions were applied, which were pH (6.5–8.5), temperature (55–65°C), hydrolysis time (30–120 min), and Alcalase® to substrate concentration (0.5–2.5%). The optimum condition was obtained at pH of 7.34, the temperature of 64.1°C, hydrolysis time of 104.2 min and Alcalase® to substrate concentration of 1.65%. It was found that the quadratic model can be used to describe the relationship between enzymatic hydrolysis conditions of ACM with DH. Verification of the model showed that at optimum condition, the predicted DH value (99.47%) was close to the experimental DH value (98.75%) (p>0.05). Lyophilized ACM hydrolysate produced under optimum condition composed of 5.76±0.17% moisture, 65.09±1.09% protein, 1.65±0.06% fat, 19.95±0.49 ash%, and 7.56±0.80% carbohydrate. This study showed that the degree of hydrolysis of the enzymatic hydrolysis of ACM catalysed by Alcalase® could be predicted using RSM.